METHODOLOGY AND ROLE OF BIOLOGY AS A SCIENCE - Xashimova Xadika Tolkunovna (Modern American Journals, 2025)
"Methods of teaching biological sciences" in the article the interaction between specialty disciplines, the combination of advanced ideas in the national and world education systems, integration of education and production, the development of modern science, technology, technology, the latest achievements of modern biological science and many years of work, Based on the experience of scientific observation and teaching this subject, the scientific and methodological foundations of this subject are considered.
Keywords: Skill, Method of Using Exercises, Purpose, Praise, Method, Ideology, Conceptual, Rationalization, Educational Program, Skill, Principle, Motivation, Methodology, Cluster, Perception.